EDUKASI PEMANFAATAN TEMULAWAK DALAM MENGATASI RISIKO STUNTING DI DESA CISASAWI, KABUPATEN BANDUNG BARAT - Evelyn Hemme Tambunan; Sapti Heru Widiyarti Djula (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Stunting remains a public health issue in Indonesia, including in West Bandung Regency (KBB). Insufficient optimal nutrition is often exacerbated by poor appetite in children under two years old (Baduta) and pregnant women. This Community Service Program (PkM) aimed to improve the knowledge, attitudes, and skills (KAS) of the community particularly mothers and Posyandu cadres in Cisasawi Village in utilizing Temulawak (Curcuma xanthorrhiza Roxb.) as a locally sourced, affordable, and sustainable complementary nutrition intervention to address stunting risk. The PkM implementation involved pre-intervention, development of educational modules and media, education and demonstration, post-intervention, and follow-up stages. Participants consisted of 32 mothers of Baduta, pregnant women, and Posyandu cadres. Results showed a significant increase in the participants’ average knowledge scores, from 58.7 (poor category) in the pre-test to 85.3 (good category) in the post-test (p < 0.05). Additionally, 93% of participants demonstrated practical skills in processing Temulawak into simple syrup or powdered gelatin. Discussion indicated that Temulawak is effective as a natural appetite stimulant due to its curcuminoid and essential oil content, supporting increased daily calorie intake, which is crucial for stunting prevention. This PkM concluded that education based on local wisdom is an effective and sustainable strategy to support community nutrition improvement programs in Cisasawi Village.